Efek Teratogenik Ekstrak Etanol Kulit Batang Pule (Alstonia scholaris R.Br) pada Tikus Wistar - Endang Kumolosasi; Andreanus A. Soemardji; Komar Ruslan W.; Hasti Yuliani (Institut Teknologi Bandung, 2004)
The teratogenic effect of ethanolic extract of âpuleâ (Alstonia scholaris R.Br., Apocynaceae) bark at repeated doses of 490 and 980 mg/kg body weight administered orally to pregnant Wistar rats for 19 days had been studied. Each dose caused miscarriage in 9.1% of the rats and mild hydrocephalus in 23.1% of the fetuses (dose 490 mg/kg body weight) and in 12.0% of the fetuses (dose 980 mg/kg body weight).